Monte Carlo Simulation of Linear Polymer Thermal Depolymerization under Isothermal and Dynamic Modes - Elena V. Bystritskaya; Oleg N. Karpukhin; Alla V. Kutsenova (International Journal of Polymer Science)
Kinetics of linear polymer thermal depolymerization under isothermal and dynamic TGA modes was simulated by the Monte Carlo method. The simulation was carried out on model arrays having the same initial degree of polymerization 𝑃𝑛=100 and different width (polydispersity index, PDI=𝑃𝑤/𝑃𝑛=1∼3) at three constant temperatures and five heating rates. Kinetics of the process in both modes is described by the Avrami equation, the exponent in which decreasing as the distribution width increases. Treatment of the model kinetic curves of degradation using the nonlinear regression method by the Avrami equation, under both isothermal and dynamic modes, gives correct activation energy and pre-exponential factor values independently of the initial PDI. Data obtained in the dynamic mode were also treated by two isoconversion methods, widely applied to kinetic analysis of TGA curves (Flynn-Wall-Ozawa method and Kissinger-Akahira-Sunose (KAS) method).